Taire ou exposer la diversité sexuelle ? Impacts des normes de genre et de l'hétéronormativité sur les pratiques enseignantes - Richard, Gabrielle (Genre, sexualité & société, 2015)
À partir de 22 entretiens et de 243 questionnaires d’enquête complétés par des enseignants du secondaire du Québec (Canada), cet article interroge l’existence de normes relatives au genre et à l’orientation sexuelle en milieu scolaire. Les résultats suggèrent que les pratiques professionnelles des enseignant(e)s, tant lesbiennes, gais et bisexuels (LGB) qu’hétérosexuel(le)s concernant l’homophobie et la diversité sexuelle sont influencées par ces normes. Trente ans après les premiers travaux sur le vécu des enseignants LGB, la littérature sur le coming out demeure centrale pour comprendre les pratiques professionnelles de ceux-ci ainsi que leurs appréhensions. Based on 22 interviews and 243 survey questionnaires filled out by high school teachers in Québec (Canada), this paper questions the existence of norms relating to gender and sexual orientation in schools. Results suggest that teachers’ professional practices regarding homophobia and sexual diversity are influenced by these norms, whether they identify as heterosexual or as lesbian, gay or bisexual (LGB). Thirty years after the first studies on LGB teachers’ experiences, the coming out literature remains central to the understanding of teachers’ apprehensions and fears, as well as their pedagogical practices.
Keywords: EDI; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; discipline; diversité sexuelle; homophobie; hétérosexisme; identités LGBTQIA2+; québec; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; école secondaire; étude qualitative; étude quantitative

The pedagogical practices of Québec high school teachers relative to sexual diversity - Richard, Gabrielle (Journal of LGBT Youth, 2015)
This article explores the ways in which teachers describe their pedagogical and intervention practices relative to sexual diversity in Québec (Canada). Three variables closely associated with teachers who report inclusive practices emerge: experiential training (based on the experience of a lesbian, gay, or bisexual [LGB] teacher), contact training (from close acquaintance with LGB individuals), and professional training. These factors impact the probability that a teacher will refer to homosexuality, intervene when homophobic incidents occur to deconstruct prejudices, and become the confidant of LGBQ students. Results are discussed based on research on minority teachers and on the roles of straight allies in education.
Keywords: EDI; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; discipline; diversité sexuelle; formations; homophobie; hétérosexisme; identités LGBTQIA2+; outils; québec; ressource en ligne; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; école secondaire

The social construction of sexuality - Seidman, Steven (W.W. Norton & Company, 2015)
In The Social Construction of Sexuality, Steven Seidman investigates the political and social consequences of privileging certain sexual practices and identities while stigmatizing others. Addressing a range of topics from gay and lesbian identities to sex work, Seidman delves into issues of social control that inform popular beliefs and moral standards. The new Third Edition features three new chapters that focus on the changing cultures of intimacy, the promise and perils of cyber intimacies, and youth struggles to negotiate independence and intimate solidarity.-- Provided by Publisher.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; hétérosexisme; intimité; premier cycle; privilèges; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques; travail; travail du sexe